IMPROVING STUDENTS’ READING COMPREHENSION OF VIII GRADE AT SMP NEGERI 1 TOLITOLI THROUGH HUMOR STORIES - Hidayati, Hidayati (Universitas Madako Tolitoli, 2019)
The objective of the research is to prove whether the use of Humor Stories is effective to improve students’ reading comprehension. This pre-experimental study use 30 students’ as a sample. They are grade VIIIE of SMP N 1 Tolitoli. The procedure of this research consist of pre-test, treatment, and post-test. The researcher give pretest and posttest to know the use of Humor Stories can improve the students’ reading coprehension or not. The result of the analysis show that Humor Stories contribute greatly to the students’ comprehension. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test is 52.13 while in the post-test improved up to 73.03. The data of this research are analyze by SPSS Program 16.0. Moreover, the Minimum mastery Criterion of English lesson is 66 (sixty-six). Then the data of both tests are analyze by using T-test, and the result show that the T-test value 15.001 was high than T-table value 2.045. it can be inferred that Humor Stories is very effective to improve students reading comprehesion.Keywords: Improving, reading comprehension, humor stories, narrative text.